Analysis of SMEs Empowerment in Bangka Belitung Islands Province in 2023 - Lintri Febriyani; Binar Kukuh Leksono; Ahmad Zulfikar; Juang Putra (International Journal of Magistravitae Management, 2023)
The Small and Medium-sized Enterprises (SMEs) sector is one of the backbones of the Indonesian economy, but it still faces various obstacles. The government aims to support SMEs through allocated funds. In the 2022 State Budget, Bangka Belitung Islands Province received an allocation of IDR 13.47 billion for the Economic Recovery cluster. Additionally, the Local Budget allocation of IDR 8.19 billion was divided into two programs: SMEs Empowerment (IDR 6.5 billion) and SMEs Development (IDR 1.69 billion). Among the SMEs, the largest sectors are Agriculture, Forestry, and Fisheries. However, SMEs in Bangka Belitung Islands Province have not fully optimized financing facilities, with only IDR 6 trillion accessed from the total credit ceiling of IDR 14.3 trillion offered by commercial banks. The proportion of People’s Business Credit/Ultra Micro Debtors to Bangka Belitung Islands Province SMEs is only 21.68 percent. Focused Group Discussions (FGDs) and surveys were conducted involving 42 SME actors to research the situation in Bangka Belitung Islands Province. The survey results highlighted that the availability of capital and limited access to marketing are the most significant obstacles for SMEs in the area. Furthermore, other challenges include inadequate technology/machinery, qualified human resources, training opportunities from relevant parties, and difficulties in obtaining raw materials. The survey also revealed that SME actors expect training in technical guidance and offline course classes, moving away from mere socialization methods.